NAVIGATING INTERGENERATIONAL TENSIONS IN DIGITAL MARKETING ADOPTION AND IMPLEMENTATION: EVIDENCE FROM INDONESIAN FAMILY MICRO-ENTERPRISES - Fatricia, Raja Sharah; Ramadhan, Raihan Fajri; Sabrina, Hanan Laras (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
Family micro-enterprises (FMEs) constitute the majority of business entities in Indonesia. Despite their vital role as the backbone of regional economies, FMEs face challenges in innovation, including intergenerational tensions during the adoption and implementation of digital marketing. Using a qualitative approach, this study involves 24 informants from 12 FMEs in Sumatra, Indonesia. By applying a dynamic capabilities (DCs) perspective, this study explores how FME successors can navigate intergenerational tensions and turn them into opportunities to adopt and implement digital marketing. The findings identify four sources of intergenerational tensions: (1) founders’ control and comparisons, (2) identity and value preservation, (3) digital literacy gaps, and (4) emotional decency. When strategically managed, these tensions can become spaces for relational negotiations among founders and successors. These negotiations depend on the successors’ DCs, which involve (1) sensing opportunities to engage, (2) seizing opportunities for experimentation, and (3) reconfiguring traditional routines for digital transformation. Therefore, this study contributes to family business and digital marketing literature by showing that DCs, in the context of FMEs, are socially embedded and developed through daily negotiations.